Encuesta virológica del Herpesvirus bovino-1 (HVB-1) en la Feria de Ganados de Medellín (1996)
ABSTRACT: Virological survey of Bovine Herpesvirus-1 (BHV-1) at the cattle fair in Medellin-Antioquia, Colombia. In order to contribute to the characterization of infectious Bovine Rhinotracheitis virus in Colombia, and attempt was made to isolate BHV-1 from 716 nasal, vaginal or preputial swabs taken during a period of six months, from 480 animals transported from long distance to the cattle fair in Medellin. Samples were inoculated on MDBK cell monolayer. It was supposed that long distance transportation would induce stress with the consequence of viral reactivation and shedding. A total of 1044 attempt were made to isolate the virus including 328 re-inoculations. No virus could be isolated from the inoculated samples. In addition nasal, vaginal or preputial samples were tested from 38 animals from a herds with a make of abortion located in Magangue (Bolivar), at the north cost of Colombia among the tested their were 25 seropositive, but again there were no isolations. However three semen samples out of 4 taken from bulls in this herd were positive by PCR. Further research is needed to define the real effect of BHV-1 infection in Colombia and particularly to the characterize biochemistry pattern of local strains and its pathogenic behavior.